Impact of a Vitamin D Replacement Algorithm in Children and Young Adults With Acute Lymphoblastic Leukemia. Issue 8 (November 2018) - Young, Jennifer; Welin, Elizabeth; Braeutigam, Carina; Gilger, Elizabeth; Lane, Adam; Salloum, Ralph
Abstract : Background: Pediatric cancer patients have a high prevalence of vitamin D deficiency. Children and young adults with acute lymphoblastic leukemia are at high risk for associated poor bone outcomes due to contributing effects of chemotherapy and supportive care. Evidence-based vitamin D guidelines are lacking in this population. Materials and Methods: This is a retrospective study following the implementation of an institutional guideline for standardized monitoring and supplementing vitamin D based on 25-hydroxyvitamin D levels and patient age. Goal 25-hydroxyvitamin D level was defined as ≥30 ng/mL and levels were checked every 3 months. Results: Over a period of 22 months, 69 patients (median age, 6.7 y) were included. At diagnosis, 42 patients (60.8%) were insufficient. Among insufficient patients at diagnosis, 83.3% became sufficient at first repeat level following supplementation. At completion of the study 95.6% of patients were sufficient. Insufficiency was more common in winter than summer at baseline (74.3% vs. 47.1%, P =0.03), though the impact of seasonality was overcome following the algorithm. Throughout the study 4 patients had supratherapeutic but nontoxic levels. Conclusions: Vitamin D replacement guidelines implemented in the pediatric and young adult acute lymphoblastic leukemia population markedly increased the percentage of vitamin D sufficient patients in a short period of time.